1992
DOI: 10.1002/mc.2940060204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, analysis, and chromosomal localization of a mouse genomic sequence related to the human papillomavirus type 18 E5 region

Abstract: The E5 open reading frame (ORF) from bovine papillomavirus type 1 (BPV 1) as well as the E5 ORFs from human papillomaviruses (HPV) type 6 and type 16 have been reported to transform immortalized rodent cells. In an analysis of murine and human tumors for the presence of putative papillomavirus-related sequences, we cloned amplified cellular sequences from the mouse cell line Eb that cross-hybridized with the E5 ORF of HPV 18. A 2.1-kb fragment termed HC1 was sequenced. In normal murine cells, it was present as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Although E5 protein was detected in a sample that was both HPV-16-and HPV-18-positive, PE-6 antiserum was considered to be specific for HPV-16 E5 because of the low amino acid sequence homology (31-3%) between HPV-16 E5 and HPV-18 E5. It was considered most unlikely that the antiserum was reacting with a cellular E5 homologue, as identified in mice by Kahn et al (1992), as no protein was identified in the HPV-negative sample or indeed in four of the HPV-16-positive samples. The detected protein was twice the expected M r of HPV-16 E5.…”
mentioning
confidence: 99%
“…Although E5 protein was detected in a sample that was both HPV-16-and HPV-18-positive, PE-6 antiserum was considered to be specific for HPV-16 E5 because of the low amino acid sequence homology (31-3%) between HPV-16 E5 and HPV-18 E5. It was considered most unlikely that the antiserum was reacting with a cellular E5 homologue, as identified in mice by Kahn et al (1992), as no protein was identified in the HPV-negative sample or indeed in four of the HPV-16-positive samples. The detected protein was twice the expected M r of HPV-16 E5.…”
mentioning
confidence: 99%
“…These fndings raised the possibility that the DNA region preceding the late ORFs, designated in the following as late upstream region (LUR), has a function for the differentiationdependent regulation of late gene expression. This possibility is supported by sequence analyses demonstrating that transcribed HPV ES-like sequences from mice and humans (Wagner et al, 1991;Kahn et al, 1992;Geisen et al, 1995) show similarities not only to ES, but also to upstream regulatory regions of genes known to be expressed in a tissue-or differentiation-specific manner (Kahn et al, 1992;Geisen, 1993;Geisen et al, 1995). Furthermore, sequences located at the 5' end of the HPV-16 and HPV-18 URRs have a pronounced similarity to sequences at the 3' end of the E50RF and the intervening sequence between the E5 and L20RFs of HPV-16 and HPV-18 (T. Kahn, unpublished results).…”
Section: Introductionmentioning
confidence: 95%
“…A cellular homologue of the papillomavirus E5 oncogene was detected as a single copy sequence in the murine genome by hybridization with a human papillomavirus type 18 (HPV 18) genomic probe [6], and a 94 bp sequence in the human genome was related to a sequence in the LCR of HPV 6 [5]. In addition, unidentified cellular sequences in skin tumours and normal tissue of mice [8,9] and sheep [10] were detected with variable frequency by DNA hybridization using different animal and human papillomavirus DNA probes at reduced stringency.…”
Section: Introductionmentioning
confidence: 99%